Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4816827
|View full text |Cite
|
Sign up to set email alerts
|

Method for automatization of the alignment of a laboratory based x-ray phase contrast edge illumination system

Abstract: Here we present a general alignment algorithm for an edge illumination x-ray phase contrast imaging system, which is used with the laboratory systems developed at UCL. It has the flexibility to be used with all current mask designs, and could also be applied to future synchrotron based systems. The algorithm has proved to be robust experimentally, and can be used for the automatization of future commercial systems through automatic alignment and alignment correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…For a detailed explanation of the method's working principle, the reader is referred to previous publications. 10,15,17 The method was adjusted for tomographic imaging by inserting a rotation axis parallel to the masks' apertures (orthogonal to the direction of phase sensitivity). If, at each rotation angle, two projections are acquired at opposing edge illumination configurations [Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a detailed explanation of the method's working principle, the reader is referred to previous publications. 10,15,17 The method was adjusted for tomographic imaging by inserting a rotation axis parallel to the masks' apertures (orthogonal to the direction of phase sensitivity). If, at each rotation angle, two projections are acquired at opposing edge illumination configurations [Figs.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18] While previously tomographic images acquired with a monochromatic synchrotron source were shown, 8 in this paper, the first tomographic images obtained from an EI XPCi system implemented with a commercial laboratory xray tube are presented. The obtained results demonstrate the superiority of phase over attenuation based imaging, as well as the feasibility of imaging at doses well within the limits of what is considered acceptable for in vivo, e.g., small animal imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to provide high resolution, quantitative phase, and dark field images [21][22][23]. Low spatial and temporal coherence is extremely well tolerated by the technique, which is also stable against thermal and mechanical stresses [24][25][26][27]. The main concept behind the EI approach is that by strongly shaping the X-ray beam in one direction and inserting a sharp absorbing element before detection, small angular deviations in the direction of propagation of the X-rays are translated into intensity modulations at the detector.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been proposed for XPCI by using synchrotron radiation, microfocal and extended labortory sources [2]. We focus here on edge illumination [3] in view of its properties of high resolution, sensitivity, robustness and achromaticity [4][5][6]. The latter is of particular interest for the study reported here, where we used the direct beam from a bending magnet, aiming at making use of a spectral distribution as broad as possible.…”
mentioning
confidence: 99%